Dangerous minds [videorecording (DVD)] - Smith, John N., 1943-; Pfeiffer, Michelle, 1957-; Dzundza, George; Vance, Courtney B.; Johnson, LouAnne (Buena Vista Home Video, 1999)
An inner-city high school teacher helps her class to believe in themselves.